Conservative Management of Massive Intraperitoneal Hemorrhage from Corpus Luteum Cyst in a Patient on Anticoagulant Therapy Post Fontan Procedure - Nabeel S. Bondagji (Journal of King Abdulaziz University: Medical Sciences, 2023)
The management of massive hemorrhage from corpus luteum cysts in patients on anticoagulant therapy was practically always surgical with significant morbidity. A case of a massive intraperitoneal hemorrhage from a ruptured corpus luteum cyst that was satisfactorily managed conservatively is reported. A 15-year old girl was diagnosed as having intraperitoneal hemorrhage. She was on anticoagulant therapy for atrial fibrillation that developed after having a Fontan procedure. The decision was made for surgical intervention. During the preoperative assessment the patient became hemodynamically stable, and thus, it was decided to continue conservative management. This is the first case report where a conservative management approach was utilized successfully in a patient who had a Fontan operation. This case illustrates that conservative management may represent a reasonable option in patients who are hemodynamically stable.